PERAN FINTECH DALAM MENINGKATKAN KUALITAS LAYANAN PADA UMKM DI WILAYAH KEMANGGISAN, JAKARTA BARAT - Risqiani, Renny; Lestari, Henny Setyo; Tajib, Erny (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2023)
In the current digital era, especially during the new normal, Micro, Small and Medium Enterprises (MSMEs) must adapt to existing conditions. The success of MSMEs can improve the national economy. Financial technology (fintech) is an innovation in the financial industry that MSMEs can utilize to increase their productivity. On average, pre-test data on Community Service (PkM) participants need to fully understand the procedures for accessing fintech and the conditions for transactions using them. This became the basis for counselling on fintech's role in improving service quality for MSMEs under the Insan Palma Sejahtera Foundation, West Jakarta. As many as 72 per cent of PKM participants have used fintech as a digital wallet, and the rest have never used it. Those who have used fintech as a digital wallet are easy to use and offer many promotions/discounts. Those who have not used it claim to be unsafe, have lots of scams, need to learn about fintech and find it difficult to use. The material presented in the counselling can increase participants' knowledge about the role of financial technology in MSMEs. Participants are motivated to use fintech to develop their businesses, significantly improving their services.